Regulation Of Location Permits For Tourism Investment - Fatikhah Kismilarsih; Simon Nahak; I Ketut Widia (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
The authority of regulating the permits of location for tourism investment is entitled to the government as a public official to control in accordance with the applicable procedures. The aims is to discover the legal norms that are the authority in providing the location permits for tourism investment. The method used was conducted by applying normative juridical law and exploiting related legal theories as an analysis device for the object being studied. The result is conflicts occur between Artcile 1 number 8 and Article 1 number 7 of the Regulations of the Ministry of Agrarian and Spatial / the Regulations of the Head of the Agency of National Land of Indonesian Republic, in the item 14 of 2018 pertaining to Location Permits, as well as its hierarchically preceding laws, which are Tourism Law dan Investment Law. The licensing is issued by vertical public officials to oversee the investors in the tourism sector who carry out their business activities to realize prosperity for all levels of society, according to the mandate of the preamble of the 1945 Constitution of the Republic of Indonesia. Any decisive action from the provincial, district and / or municipal governments in consonance with the applicable provisions is definitely necessary to draft regional regulations which exclusively governing the Norms, Standards, Procedures, and Provisions concerning supervision, guidance and issuance of permits for tourism investment locations, so that there is a legal umbrella for the law enforcement officers in issuing the Location Permits for Tourism Investment.